ISLAM, MULTICULTURALISM AND NATION-BUILDING IN THE POST-TRUTH AGE: THE EXPERIENCE OF INDONESIA - Widiyanto, Asfa (Journal of Al-Tamaddun, 2019)
Nation-building in postcolonial Asia, including Indonesia, was concerned most notably with drawing and imagining the boundaries of the nation. This process was and is an intriguing process. The notion of ‘natives’ and ‘non-natives’ is part of this complex process of nation-building. It is of significance to explore the role of Islam in nurturing nation-building and multiculturalism in Indonesia, since Islam is the religion of the majority of the population, and accordingly constitutes a dominant societal culture. A particular attention is given to the role of the Muhammadiyah and the Nahdlatul Ulama, the mainstream Islamic civil society organisations in the country. This paper examines the interplays between Islam, multiculturalism and nation-building in the present-day Indonesia, by looking specifically to the context of post-truth age which poses both challenges and opportunities to the country. I argue that the prospects for multiculturalism and nation-building in Indonesia are in some ways determined by the role and agency of Islamic civil society organisations in dealing with the new era which consequently alters the contours of religious authority.